2022
DOI: 10.1039/d2ta03748c
|View full text |Cite
|
Sign up to set email alerts
|

Surface stability of ionic-liquid-passivated mixed-cation perovskite probed within situphotoelectron spectroscopy

Abstract: A passivation treatment is proposed that improves perovskite photovoltaic device performance and stability to annealing in dry environments. A rationale is presented for the observed loss of stability on heating in wet environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Another precursor additive OMIMCl with a similar structure was adopted to slow down the crystallization, which was ascribed to the higher boiling point of the IL than DMF and DMSO. 107 Zheng et al reported that with an IL additive TBAPF 6 , PF 6…”
Section: Grain Size Enlargementmentioning
confidence: 99%
See 1 more Smart Citation
“…Another precursor additive OMIMCl with a similar structure was adopted to slow down the crystallization, which was ascribed to the higher boiling point of the IL than DMF and DMSO. 107 Zheng et al reported that with an IL additive TBAPF 6 , PF 6…”
Section: Grain Size Enlargementmentioning
confidence: 99%
“…Another precursor additive OMIMCl with a similar structure was adopted to slow down the crystallization, which was ascribed to the higher boiling point of the IL than DMF and DMSO. 107 Zheng et al reported that with an IL additive TBAPF 6 , PF 6 − anions could partially substitute the halide ions and chelate Pb 2+ cations, which was beneficial to slow down the crystal growth. 108 In addition, the alkyl chain in TBA + may also alter the crystallization, enabling an enlarged perovskite grain size with improved surface coverage.…”
Section: Improvement Of Crystalline Propertymentioning
confidence: 99%
“…The use of ionic liquids (ILs) seems to be one of the potential solutions to some of the perovskite solar cells problems, due to their high conductivity, potential for chemical “tuning” of the structure, and relatively smaller environmental impact. , Maniyarasu et al studied the role of IL additives in improving the stability of perovskite is investigated by in situ photoemission spectroscopy while increasing the temperature. A small amount (0.3 mol %) of 1-octyl-3-methylimidazolium chloride was incorporated into FA 0.9 Cs 0.1 PbI 3 perovskites.…”
Section: In Situ Characterization Of Metal Halide Perovskitesmentioning
confidence: 99%
“…Control of the composition and morphology of perovskite thin films is key to enhancing both the stability and performance of devices. Defects are known to accelerate the decomposition of perovskites on exposure to atmospheric conditions, as well as through ion migration during device operation. Grain size has also been shown to influence perovskite degradation, with larger grains proving to be more robust when exposed to moisture …”
Section: Introductionmentioning
confidence: 99%